2014
DOI: 10.1371/journal.pone.0087266
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity and Initial Oligomerization of PrP106–126 Studied by Replica-Exchange and Conventional Molecular Dynamics Simulations

Abstract: Prion diseases are marked by cerebral accumulation of the abnormal isoform of the prion protein. A fragment of prion protein composed of residues 106–126 (PrP106–126) exhibits similar properties to full length prion and plays a key role in the conformational conversion from cellular prion to its pathogenic pattern. Soluble oligomers of PrP106–126 have been proposed to be responsible for neurotoxicity. However, the monomeric conformational space and initial oligomerization of PrP106–126 are still obscure, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…Prion protein : The study of PrP(106–126) by Ning et al . also describes the formation of the trimer and the tetramer.…”
Section: Computational Studiessupporting
confidence: 66%
See 4 more Smart Citations
“…Prion protein : The study of PrP(106–126) by Ning et al . also describes the formation of the trimer and the tetramer.…”
Section: Computational Studiessupporting
confidence: 66%
“…PrP is such ap eptide and was studied in an all-atom REMD simulation. [173] The results of this study indicated that the dimerizationw as driven by hydrophobic interactions; however,t he conformational flexibility was similart ot hat of the monomer,w ith no increasei nb-sheet content observed. From ac oarse-grained simulation of the larger PrP(121-231)p rotein it was concluded that very little intermolecular b-sheet structure could be observed in the dimer intermediate.…”
Section: Moleculars Imulations Of Dimer Formationmentioning
confidence: 59%
See 3 more Smart Citations